Conversion of styrene into benzaldehyde and styrene epoxide over MgCoAl-LDH catalysts - Tien Thao, Nguyen; Long, Dang Van; Hoan, Dinh Minh (Vietnam Journal of Science and Technology, 2017)
Co-containing hydroxides have been successfully synthesized by the co-precipitation of starting-metal salts. The obtained materials were characterized by some physical means including XRD, EDS, BET… It is found that Co2+ ions are present in the layered double hydroxide (LDH) sheets. The presence of cobalt ions in LDH plays as active sites for the oxidation of styrene with air. The catalysts exhibited a very high activity in the conversion of styrene into two main products (benzaldehyde and styrene oxide). The highest styrene conversion is about 90-95% and the total selectivity to benzaldehyde and styrene oxide is in the range of 80-85% under reported experimental conditions.